Interpersonal Meaning Analysis of Taylor Swift Song Lyrics in Fearless (Taylor’s Version) Album - Salma Nabilla Maulida (Passage: Journal of English Language and Literature, 2023)
The study examines the language phenomenon found in an American singer-songwriter’s album. Specifically, this study aims to analyze the interpersonal meaning used by Taylor Swift in Fearless (Taylor’s Version) Album. Regarding data source, three songs which represent a whole album, particularly Love Story, Hey Stephen, and White Horse were selected. Qualitative design was applied in this research to identify mood system and the use of modality in the selected song lyrics. In classifying the type of mood, a theory proposed by Strauss et al. (2018) was used. Meanwhile, the theory given by Halliday (2014) was employed to discover the modality in the song lyrics. It was also supported by some theories from Systemic Functional Language (SFL) scholars, such as Gerot and Wignell (1994) and Eggins (2004). The findings discover that the singer only uses three types of mood: declarative, interrogative, and imperative. Since declarative mood becomes the most dominant type, it can be concluded that the album mostly expresses the singer’s ideas. The singer also reveals her certainty by using different degrees of modality in statements that are found in declarative clauses. By determining the dominant mood and the degree of modality, the study result is expected to be useful for the listeners to increase their understanding of the meaning and context consisting of music albums.